Respostas
respondido por:
0
a) delta=(-4)²-4*2*(-16)
delta= 16+128=144
x=-(-4)+ou- 12/4
x1=4+12/4=4
x2=4-12/4=-2
S=x1+x2=4+(-2)= 2
P=x1*x2=4(-2)=-8
b)delta=(-1)²-4*1*(-6)
delta=1+24=25
x=-(-1)+ou-5/2
x1=1+5/2=3
x2=1-5/2=-2
S=x1+x2=3+(-2)=1
P=x1*x2=3(-2)=-6
delta= 16+128=144
x=-(-4)+ou- 12/4
x1=4+12/4=4
x2=4-12/4=-2
S=x1+x2=4+(-2)= 2
P=x1*x2=4(-2)=-8
b)delta=(-1)²-4*1*(-6)
delta=1+24=25
x=-(-1)+ou-5/2
x1=1+5/2=3
x2=1-5/2=-2
S=x1+x2=3+(-2)=1
P=x1*x2=3(-2)=-6
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás